Electrosteric colloidal stabilization for obtaining SrTiO3/TiO2 heterojunction: Microstructural evolution in the interface and photonics properties - Amoresi, Rafael A.C. [UNESP]; Teodoro, Vinícius; Teixeira, Guilhermina F. [UNESP]; Li, Maximo S.; Simões, Alexandre Z. [UNESP]; Perazolli, Leinig A. [UNESP]; Longo, Elson [UNESP]; Zaghete, Maria A. [UNESP] (Elsevier, 2018)
Researches on solids heterojunctions has proven to be an important field for technological applications due to synergism achieved by interface phenomena. In this work, we present an understanding of SrTiO3/TiO2 interface and its effects on structural and microstructural characteristics, and relate them to photoluminescence properties of heterojunctions obtained by a simple method. It was observed that SrTiO3 proportion directly influences the structural order-disorder, as observed by X-Ray diffraction, Raman spectroscopy and Transmission electron microscopy. Photoluminescence behavior of heterojunction with 1% of SrTiO3 showed a shift to blue emission region compared to TiO2, and enhanced of emission intensity compared to SrTiO3, resulted from defects generated by interface effects, attracting possible applications on selective color emitter. Therefore, we conclude that in same materials phases, nature and concentration of structural defects has strong dependence of SrTiO3 concentration, which leads to different photoluminescence properties.
Keywords: Heterojunction; Interface; Photonic; SrTiO3/TiO2